EVALUATION STUDY MENPORA CUP WOMEN’S U-17 TIERED LEAGUE COMPETITION - Adam, Angga Muhammad; Moch. Asmawi; Hernawan; Suharto, Taufik Hidayat (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to evaluate the 2019 Menpora Cup Women’s U-17 Tiered League Competition Program. This study used a qualitative technique with an evaluation approach using the Context, Input, Process and Product (CIPP) model. The method of collecting data is triangulation using questionnaires, interviews, document studies and observation. The result of the research show that in: (1) Context Evaluation: has a very strong legal basis and government policy, with good intentions and goals, but not yet targeted. (2) Input evaluation: participants, organization, financing and committee have not been carried out properly and need to be improved in accordance with the development of the Menpora Cup Women’s U-17 tiered league competition every year. (3) Process Evaluation: sporting competition rules that must always be updated in accordance with football developments, competition implementation still needs to be maximized properly. (4) Product Evaluation: increasing public participation and interest in organizing the Menpora Cup Women’s U-17 tiered league competition every year, the role of the media in publication and promotion of sports to the community is increasingly being expanded, and efforts to find potential sports athletes from the community that need to be developed optimized. However, athletes’ achievements have not contributed much to world-class achievements.